The Beginnings of the Modern Philosophy of Music in England - Kassler, Jamie Croy (Burlington Ashgate, 2004)
In 1677 a slim quarto volume was published anonymously as A Philosophical Essay of Musick. Written by Francis North (1637-85), chief justice of the Common Pleas, the Essay is in the form of a legal case argued from an hypothesis. Utilising the pendulum as his hypothesis, North provided a rationale from mechanics for the emerging new musical practice we now call 'tonality'. He also made auditory resonance the connecting link between acoustical events in the external world and the musical meanings the mind makes on the basis of sensory perception. Thus began the modern philosophy of music that culminated with the work of Hermann von Helmholtz. As a step towards understanding this tradition, Jamie C. Kassler examines the 1677 Essay in its historical context. After assessing three seventeenth-century criticisms of it and outlining how one critic developed some implications in the Essay, she summarises the basic principles that have guided the modern philosophy of music from its beginnings in the 1677 Essay. The book includes an annotated edition of the Essay as well as the comments of the three critics.
The Beginnings of the Modern Philosophy of Music in England: Francis North's A Philosophical Essay of Musick (1677) with comments of Isaac Newton, Roger North and in the Philosophical Transactions
Keywords: North, Francis -- 1637-1685; Newton, Isaac -- Sir -- 1642-1727; North, Roger -- 1651-1734; Music philosophy and esthetics